2018
DOI: 10.3389/fendo.2018.00563
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Lumbar Vertebral Bone Marrow and Paraspinal Muscle Fat Compositions—An Investigation by Chemical Shift Encoding-Based Water-Fat MRI

Abstract: Purpose: Advanced magnetic resonance imaging (MRI) methods enable non-invasive quantification of body fat situated in different compartments. At the level of the lumbar spine, the paraspinal musculature is the compartment spatially and functionally closely related to the vertebral column, and both vertebral bone marrow fat (BMF) and paraspinal musculature fat contents have independently shown to be altered in various metabolic and degenerative diseases. However, despite their close relationships, potential cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 47 publications
5
47
1
Order By: Relevance
“…Bone and muscle measures were made in the appendicular anatomy, which could be restricted in generalization to more central sites such as the hip and spine. However, one previous study by Sollmann and colleagues observed similar correlations in fat fraction distributions between paraspinal muscles and vertebral bone marrow, albeit in a small cohort of 24 postmenopausal women ( r = 0.457, p = 0.025) …”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Bone and muscle measures were made in the appendicular anatomy, which could be restricted in generalization to more central sites such as the hip and spine. However, one previous study by Sollmann and colleagues observed similar correlations in fat fraction distributions between paraspinal muscles and vertebral bone marrow, albeit in a small cohort of 24 postmenopausal women ( r = 0.457, p = 0.025) …”
Section: Discussionmentioning
confidence: 69%
“…Only one study has been able to demonstrate this relationship so far but only among 24 postmenopausal women ( r = 0.457, p = 0.025) with minimal adjustment for confounders. Meanwhile, the authors found no association among the 15 premenopausal women ( p = 0.907) . No further studies have directly examined this relationship.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…As shown in previous studies, bone marrow PDFF values show specific distribution patterns inter-and also intra-individually, depending on the topography within the lumbar spine, with increasing PDFF from cranial to caudal (L1 to L5) 3,9-11 . Furthermore, an age-dependent correlation between the structural composition of the local lumbar musculature and vertebral bone marrow fat has been described recently 12 . A systematic analysis of the functional impact associated with these pathophysiological processes using isometric strength measurements showed that an increased fatty infiltration of the paraspinal muscles significantly correlated with reduced muscle strength 13,14 .…”
mentioning
confidence: 99%